2013
DOI: 10.1007/s13361-013-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Azomethine Ylide Formation and Its Covalent Entrapment by Fulleropyrrolidine Derivatives During MALDI Analysis

Abstract: Two novel monofunctionalized fulleropyrrolidine derivatives (Prato adducts) were prepared and characterized by matrix-assisted laser desorption/ionization (MALDI) and electrospray ionization (ESI). MALDI experiments conducted in the positive-ion mode on pure and mixed samples of both monofunctionalized fullerene derivatives revealed the efficient formation of bisadducts (in the case of the pure samples) and mixed bisadducts (in the case of a mixed sample). Bisadducts were not observed in the ESI experiments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The formation of fullerene ions was accounted for by the elimination of the corresponding 1,3‐ and 1,2‐dipole fragments through a retro‐cycloaddition reaction. The in situ generation of these ylides has been demonstrated by trapping this reactive intermediate under MS conditions with a fullerene monoadduct which acts as dipolarophile, leading to the formation of fullerene bis‐adducts …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of fullerene ions was accounted for by the elimination of the corresponding 1,3‐ and 1,2‐dipole fragments through a retro‐cycloaddition reaction. The in situ generation of these ylides has been demonstrated by trapping this reactive intermediate under MS conditions with a fullerene monoadduct which acts as dipolarophile, leading to the formation of fullerene bis‐adducts …”
Section: Methodsmentioning
confidence: 99%
“…The in situ generation of these ylides has been demonstrated by trapping this reactive intermediate under MS conditions with a fullerene monoadduct which acts as dipolarophile, leading to the formation of fullerene bis-adducts. [24] Under positive ESI conditions, pyrrolidinofullerenes provide protonated molecules [M+H] + . [25] It is well known that pyrrolidine is a weak base and theoretical calculations and experimental data reveal that the fullerene moiety reduces dramatically the basicity of the nitrogen atom of the pyrrolidine ring.…”
mentioning
confidence: 99%
“…[13][14][15] Earlier mass spectrometry-based studies have concentrated on the 1 characterization of the retro-cycloaddition reaction evaluating the conditions leading to the 2 complete loss of the ligand. [16][17][18][19] In an earlier MALDI investigation, we showed that the 3 released ylide ligand can efficiently re-attach to an intact adduct, [20] thereby potentially 4 falsifying efforts aimed at the elucidation of the true amount of ligand attainment in the starting 5 material. [21] Following this earlier investigation, we studied several other fulleropyrrolidines 6 and with the Prato adduct discussed in this note we discovered a system in which neutral and The fulleropyrrolidine adducts were prepared as described previously.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Following this earlier investigation, we studied several other fulleropyrrolidines 6 and with the Prato adduct discussed in this note we discovered a system in which neutral and The fulleropyrrolidine adducts were prepared as described previously. [20] Unreacted C60 was 13 removed from the raw product which was then used without further purification, as the multi-14 ligated adducts were the target of this study. A stock solution of the raw product in toluene (1 15 g/L) was prepared and further diluted with dichloromethane and methanol in a 1:1 ratio 16 resulting in a solution with a monoadduct concentration of roughly 5 x 10 -5 mol/L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation